2013
DOI: 10.2298/vetgl1302055p
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of G class antibodies to antigens of lyme disease causes in dogs in Vojvodina, Serbia

Abstract: Lyme disease is a multisystemic disease, zoonotic in nature, caused by the Borrelia burgdorferi sensu lato complex. In the continent of Europe, these spirochetes are predominantly transmitted by ticks of the genus Ixodes. Small mammals and birds have particular significance as reservoirs of the cause of lyme disease. The objective of these epidemiological investigations was to determine the value of IgG seroprevalence to Borrelia burgdorferi and to secure the geographic distribution of seropositive dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…IgG antibodies by ELISA (recomWell Borrelia canis IgG, Mikrogen, Germany) and Western blot assay (recomBlot Borrelia Canis IgG, Mikrogen, Germany). In that study, most of the positive findings were in South Bačka district area (Potkonjak et al, 2013b). In accordance with Potkonjak et al (2013b), Kovačević Berić et al reported lower average seroprevalence (0.07%) in dogs from North Bačka district (Berić .…”
Section: Borrelia Burgdorferi Sensu Lato (Sl) Complexsupporting
confidence: 84%
“…IgG antibodies by ELISA (recomWell Borrelia canis IgG, Mikrogen, Germany) and Western blot assay (recomBlot Borrelia Canis IgG, Mikrogen, Germany). In that study, most of the positive findings were in South Bačka district area (Potkonjak et al, 2013b). In accordance with Potkonjak et al (2013b), Kovačević Berić et al reported lower average seroprevalence (0.07%) in dogs from North Bačka district (Berić .…”
Section: Borrelia Burgdorferi Sensu Lato (Sl) Complexsupporting
confidence: 84%
“…In Europe, I. ricinus is the main vector, but the roles of many vertebrates as potential reservoir hosts are still unknown (Franke et al, 2013). Previous seroepidemiological studies in Serbia confirmed that domestic dogs are exposed to B. burgdorferi s.l (Obrenović et al, 2015;Potkonjak et al, 2013), while a high diversity of Borrelia species (B. burgdorferi s.s., Borrelia afzelii, B. lusitaniae, B. garinii, Borrelia bavariensis, and Borrelia valaisiana) were confirmed in I. ricinus ticks collected from vegetation (Ćakić et al, 2019;Tomanović et al, 2008).…”
Section: Role Of Jackals and Foxes In The Epidemiology Of Tick-borne mentioning
confidence: 99%
“… I. ricinus Ticks 2.8 19.35 PCR-Seq PCR [ 165 ] [ 166 ] A. phagocytophilum I. ricinus , D. reticulatus , Hae. concinna , dog, golden jackal 0.9–15.5 IFAT, PCR-Seq, mf qPCR [ 158 , 161 , 163 , 165 , 166 , 174 , 176 , 178 , 179 ] N. mikurensis I. ricinus 4.2 PCR-Seq [ 12 , 165 , 166 ] E. canis Dog Case report, 16% IFAT, PCR-Seq [ 152 , 180 ] R. monacensis I. ricinus 14.8–22.5 PCR-Seq, mf qPCR [ 165 , 166 , 172 175 ] R. helvetica I. ricinus 7.4–54.0 PCR-Seq, mf qPCR [ 172 175 ] R. raoultii D. reticulatus 5.6 PCR-Seq, mf qPCR [ 165 , 172 ] …”
Section: Introductionmentioning
confidence: 99%
“…concinna , Rh. Sanguineus 3.8–62.9 PCR-Seq [ 174 , 183 ] B. burgdorferi s.l I. ricinus , dog, rodent 8.1–54.2 DF, IFAT, ELISA, WB, PCR [ 146 , 147 , 150 152 , 154 156 , 174 , 176 ] B. afzelii I. ricinus 7.0–75.0 Isolation, PCR-Seq, PCR/RFLP, RT-PCR [ 151 , 152 , 158 160 , 178 ] B. garinii I. ricinus , D. reticulatus , red fox 0.8–4.9 Isolation, PCR-Seq, PCR/RPLF [ 12 , 152 , 158 162 , 178 ] B. burgdorferi s.s I. ricinus , red fox 0.8–22.2 PCR-Seq, PCR/RFLP [ 12 , 152 , 159 , 178 ] B. valaisiana I. ricinus 1.4–3.8 Isolation, PCR-Seq, PCR/RFLP, mf qPCR [ 158 , 160 163 , 178 ] B. lusitaniae …”
Section: Introductionmentioning
confidence: 99%